Gaya Kepemimpinan Lurah Besusu Tengah Kecamatan Palu Timur Kota Palu - Ramadan Ramadan (Jurnal ADMINISTRATOR, 2021)
This study aims to find out how the Leadership Style of the Besusu Tengah Village Head, East Palu District, Palu City. The basis of this research is qualitative, while the type of research used is descriptive. Data collection techniques are carried out in two ways, namely library research and field studies. The types of data used in this study are primary data (data obtained directly through the interview process) and secondary data (data obtained from books, documents, and other sources in accordance with the research to be conducted). This study uses the theory of Harsey and Blanchard in Harbani Pasolong about Leadership Style, namely, there are 4 (four) aspects/dimensions, namely the style of instruction, consultation, participation and delegation. Based on the results of the research obtained from informants and empirical facts that the authors observed as well as analysis in the field, it was concluded that from the 3 (three) aspects mentioned above, the authors have studied that what has been going well are the aspects of instruction, consultation, and delegation. However, what has not gone according to the expectations of the community is the aspect of participation where the residents of the Besusu Tengah village have not maximally participated in the development and cleanliness of the environment in the Besusu Tengah village, because the schedule and time have not been set, therefore the community usually cannot attend because usually suddenly there are a sudden announcement to participate in the environmental cleanliness of the Besusu Tengah village, East Palu District, Palu City